Curved Sandwich Panels. Issue 2 (1st September 2021) - Lange, Jörg; Groche, Peter; Schäfer, Stefan; Grimm, Sören; Moneke, Mathias; Reising, Jakob; Kehl, Marvin
Abstract: Due to their excellent combination of space enclosing, heat insulating and supporting function, steel sandwich panels – mostly flat – are used for roofs and walls of standard industrial buildings. Because freely formed structures generally are playing an increasing role in contemporary architecture, curved sandwich panels would offer a high potential to architectural design. Simultaneously, the advantageous load‐bearing capacity could further increase the benefits of their usage. The necessary design strategy, the manufacturing technology for the curved cover plates and their overall mechanical behavior – all of these 3 main keys have been investigated in an interdisciplinary research project with architects, structural‐ and mechanical engineers. It has been one of the main goals in this project to find an applicable, efficient strategy for singularly produced panels (lot size 1: serial production with quantity = 1) in favour of a maximum flexibility for individual geometries.